2019
DOI: 10.3892/mco.2019.1871
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression presenting as intestinal perforation in non‑small cell lung cancer treated with anti‑PD‑1: A case report

Abstract: Pseudoprogression is not frequently observed in patients with non-small cell lung cancer (NSCLC) who are treated with immune checkpoint inhibitors. We report on a case of pseudoprogression, which was presented as intestinal perforation after pembrolizumab immunotherapy for NSCLC. A-54-year-old man with stage IV NSCLC received pembrolizumab therapy. The patient was admitted to our hospital because of acute abdominal pain and the computed tomography scan revealed diffuse wall thickening of the small bowel with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Here we describe a case of small bowel perforation attributed to a primary SCCHN metastasizing to the GIT in the setting of treatment with PD-1 inhibitors. This is the first reported case of a palatine tonsillar cancer metastasizing to the small bowel, and adds to the small number of reported bowel perforations resulting from treatment with monoclonal PD-1 and PD-L1 inhibitors in the presence of metastatic tumor from any primary source [10][11][12][13].…”
Section: Introductionmentioning
confidence: 72%
“…Here we describe a case of small bowel perforation attributed to a primary SCCHN metastasizing to the GIT in the setting of treatment with PD-1 inhibitors. This is the first reported case of a palatine tonsillar cancer metastasizing to the small bowel, and adds to the small number of reported bowel perforations resulting from treatment with monoclonal PD-1 and PD-L1 inhibitors in the presence of metastatic tumor from any primary source [10][11][12][13].…”
Section: Introductionmentioning
confidence: 72%
“…One case report demonstrated that cytotoxic T lymphocytes positive for CD3 and CD8 were infiltrated into the metastatic tumor in a patient who experienced PsP. 22 As T-lymphocyte infiltration in tumor and stroma has been reported as a promising prognostic factor in NSCLC patients, 23 the better outcome in PsP patients may in part be associated with the favorable effect of T-cell infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudoprogression is an atypical pattern of response. In some cases, it could be associated with dramatic symptoms, such as tamponade and pleural effusions [6], intracranial hypertension [7], or bowel perforation [8]. As in our two cases, pseudoprogression may also be late-onset after ICI initiation [9,10].…”
Section: Discussionmentioning
confidence: 50%